Uranium(IV) halide (F-, Cl-, Br-, and I-) monoarene complexes. - Halter, Dominik; la Pierre, Henry Storms; Heinemann, Frank Wilhelm; Meyer, Karsten (Inorganic Chemistry, 2014)
The syntheses of four nearly isostructural uranium(IV) monoarene complexes, supported by the arene anchored tris(aryloxide) chelate, [((Ad,Me)ArO)3mes](3-), are reported. Oxidation of the uranium(III) precursor [(((Ad,Me)ArO)3mes)U], 1, in the presence of tetrahydrofuran (THF) results in THF coordination and distortion of the equatorial coordination sphere to afford the uranium(IV) η(6)-arene complexes, [(((Ad,Me)ArO)3mes)U(X)(THF)], 2-X-THF, (where X = F, Cl, Br, or I) as their THF adducts. The solvate-free trigonally ligated [(((Ad,Me)ArO)3mes)U(F)], 2-F, was prepared and isolated in the absence of coordinating solvents for comparison.